A novel approach for independent budgeting of fossil fuel CO2 over Europe by 14CO2 observations - Levin, Ingeborg (Universitätsbibliothek der Universität Heidelberg, 2003)
Long-term atmospheric 14CO2 observations are deployed to quantify fossil fuel derived CO2 concentrations at a regional polluted site, and at a continental mountain station in south-west Germany. Fossil fuel CO2 emission rates for the relevant catchment areas are obtained by applying the Radon-Tracer-Method. They are shown to compare well with statistical emissions inventories but reveal a larger seasonality than assumed earlier, thus contributing significantly to the observed CO2 seasonal cycle over Europe. Based on the present approach, emissions reductions on the order of 5-10% are detectable for catchment areas of several hundred kilometres radius, as anticipated within a five-years commitment period of the Kyoto Protocol. Still no significant change of fossil fuel CO2 emissions is observed at the two sites over the last 16 years.